Overcoming Barriers to Referral for Chimeric Antigen Receptor T Cell Therapy in Patients with Relapsed/Refractory Diffuse Large B Cell Lymphoma - Hoffmann, Marc S.; Hunter, Bradley D.; Cobb, Patrick W.; Varela, Juan C.; Munoz, Javier (Transplantation and cellular therapy, 2023)
•Chimeric antigen receptor (CAR) T cell therapy has shown efficacy and a manageable safety profile in relapsed/refractory diffuse large B cell lymphoma.•Several logistical/financial barriers prevent timely access to CAR-T therapy.•Collaboration between oncologists and treatment centers can overcome these barriers. Diffuse large B cell lymphoma (DLBCL) is the most prevalent subtype of non-Hodgkin lymphoma. Although outcomes to frontline therapy are encouraging, patients who are refractory to or in relapse after first-line therapy experience inferior outcomes. A significant proportion of patients treated with additional lines of cytotoxic chemotherapy ultimately succumb to their disease, as established in the SCHOLAR-1 study. Chimeric antigen receptor (CAR) T cell therapy is a novel approach to cancer management that reprograms a patient's own T cells to better target and eliminate cancer cells. It was initially approved by the US Food and Drug Administration for patients with relapsed/refractory (r/r) DLBCL as a third line of treatment. Based on recently published randomized data, CAR-T therapy (axicabtagene ciloleucel and lisocabtagene maraleucel) also has been approved as a second line of treatment for patients who are primary refractory or relapse within 12 months of first-line therapy. Despite the proven efficacy in treating r/r DLBCL with CD19-directed CAR-T therapy, several barriers may prevent eligible patients from receiving treatment. Barriers to CAR-T therapy include cost of therapy, patient hesitancy, required travel to academic treatment centers, nonreferrals, poor understanding of CAR-T therapy, lack of caregiver support, knowledge of available resources, and timely patient selection by referring oncologists. In this review, we provide an overview of the FDA-approved CD19-directed CAR-T cell therapies (tisagenlecleucel, axicabtagene ciloleucel, and lisocabtagene maraleucel) from pivotal clinical trials and supporting real-world evidence from retrospective studies. In both clinical trials and real-world settings, CAR-T therapy has been shown to be safe and efficacious for treating patients with r/r DLBCL: however, several barriers prevent eligible patients from accessing these therapies. Barriers to referrals for CAR-T therapy are described, along with recommendations to improve collaboration between community oncologists and physicians from CAR-T therapy treatment centers and subsequent long-term care of patients in community treatment centers.